The inclusion of surface characteristics in equations for turbulence closure - Telles,A.S. (2000)
The possibility of the inclusion of the charactheristics of surfaces in the formulation of closure equations for the turbulent fluxes is considered. The general formulation is presented in the form of an expression which, with respect to the fluid motion, it is a general constitutive equation as proposed by Noll, and to which, it was added the explicit dependence upon the wall configuration. Restrictions imposed by frame indifference, and by the symmetry group of the surface are examined.